Labor market effects from the Panama Papers: evidence from Brazil - Barros, Armando Henrique Zeviani Monteiro de (2024)
This paper analyzes the labor market and career consequences of being named in the Panama Papers – a set of leaked documents containing information on individuals with activity in tax sanctuaries – in the Brazilian context. The main hypothesis is that their outcomes could be affected via two margins: behavioral and reputational. Leveraging the ICIJ Leaks database and matched employer-employee data for labor market outcomes, the event-study econometric regressions suggest that exposed individuals face more career stability and have higher earnings after the intervention. In particular, we infer those named were shielded from the Brazilian crisis then; hence, exposure in the Panama Papers had a net positive effect on their careers. Furthermore, the suggestion is that the mechanism behind these results is behavioral rather than reputational.